1997
DOI: 10.1086/647654
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Interhospital Transmission of Extended-Spectrum β-Lactam-Resistant Klebsiella pneumoniae in the United States, 1986 to 1993

Abstract: These data provide evidence of interhospital transmission of ESBLR K pneumoniae in one region of the United States and stress the interrelationship between hospitals when trying to control antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The outbreak was also fueled by hospital-to-hospital transfers, as shown by the very large number of health care institutions where ESBLPE-positive patients were transferred to or from. These data are in keeping with several reports [13,23,44]. A recent study examined the first SHV-4 extended-spectrum blactamase-producing K. pneumoniae strain isolated in 14 French hospitals, mainly in the Paris area [44].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The outbreak was also fueled by hospital-to-hospital transfers, as shown by the very large number of health care institutions where ESBLPE-positive patients were transferred to or from. These data are in keeping with several reports [13,23,44]. A recent study examined the first SHV-4 extended-spectrum blactamase-producing K. pneumoniae strain isolated in 14 French hospitals, mainly in the Paris area [44].…”
Section: Discussionsupporting
confidence: 88%
“…In 1993, 9.4% of K. pneumoniae isolates in the National Nosocomial Infection System were ESBLPE [23]. The same year, the Paris Area Public Hospital Surveillance Network found that as many as 24.8% of K. pneumoniae isolates were ESBLPE, indicating an outbreak more extensive than any other reported worldwide [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clonal spread did not explain the overall prevalence of isolates expressing an ESBL in each hospital, since unrelated ESBL organisms were also identified. In addition, there was no clear evidence of significant clonal spread from hospital to hospital or country to country, although previous studies have identified more widespread transmission [26]. These data did identify distinct isolates expressing similar b-lactamases with more unusual pI values.…”
Section: Discussionmentioning
confidence: 58%
“…On a broader scale, identification of resistant clones with extensive geographic distribution may provide insight into strain virulence and pathogenesis and also may result in public health interventions such as vaccination and antimicrobial restrictions aimed at reducing the spread of the pathogen and the resistance problem [13,14,32,33].…”
Section: Application Of Molecular Methods In a Global Surveillance Symentioning
confidence: 99%